2021
DOI: 10.3390/su13063265
|View full text |Cite
|
Sign up to set email alerts
|

Are Technological Innovation and Foreign Direct Investment a Way to Boost Economic Growth? An Egyptian Case Study Using the Autoregressive Distributed Lag (ARDL) Model

Abstract: Both technological innovation and foreign direct investment have received widespread attention in the literature on their role in promoting economic growth. Therefore, this study aims to test the relationship between foreign direct investment, technological innovation, and economic growth of the Egyptian economy during the period between 1990–2019 using the autoregressive distributed lag model simultaneous integration test. Our findings show of the ARDL (Autoregressive Distributed Lag) model estimation a joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
5
26
1
Order By: Relevance
“…Firstly, findings support the theory of endogenous growth which indicates that innovation stimulates economic growth. In addition, findings approve the neoclassical growth theory which suggests that foreign investment through multinational companies increases wealth in host nations and this situation enables the realization of growth much faster than domestic savings (Mohamed et al, 2021). The study present practical implications for governments and stakeholders.…”
Section: Limitations and Future Implicationssupporting
confidence: 60%
See 3 more Smart Citations
“…Firstly, findings support the theory of endogenous growth which indicates that innovation stimulates economic growth. In addition, findings approve the neoclassical growth theory which suggests that foreign investment through multinational companies increases wealth in host nations and this situation enables the realization of growth much faster than domestic savings (Mohamed et al, 2021). The study present practical implications for governments and stakeholders.…”
Section: Limitations and Future Implicationssupporting
confidence: 60%
“…Adak's (2015) study emphasized the impact of technological innovation on economic growth. Indeed, in the globalizing world, the differences between countries in technology and innovation explain the differences in economic growth between countries (Mohamed et al, 2021). Likewise, Maradan et al (2017) found that technological innovation is one of the most essential determinants of economic growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Double cycle" and the synergy of industrial upgrading can realize the innovation chain as the leading factor in the "four chains" of innovation chain, supply chain, industrial chain, and value chain, and drive highquality economic development [33]. Meanwhile, industrial upgrading could strengthen green technological innovation and green development, forming a mutually reinforcing pattern of ecological protection and high-quality development through ecological protection, and promoting the improvement of ecological protection through high-quality development [34,35].…”
Section: "Dual Cycle" and Industrial Upgrading Impact On High-quality...mentioning
confidence: 99%